An experimental inter-expert telepathology network using static imaging. Issue 10 (1st October 2001) - Tucker, J H; Busch, C; Spatz, A; Wells, C; Brugal, G
Abstract : Aims —To set up a network for remote consultation using static imaging telepathology via Internet connection between pathologists in different European countries, and to collect some numerical and subjective impressions on the usefulness of this form of telepathology. Methods —A static image remote consultation network between 11 pathologists in nine European countries was set up; all pathologists were equipped with the same telepathology system. The pathologists formed three subject oriented subgroups concerned with prostate, melanoma, and soft tissue sarcoma pathology. Each pathologist sent and received a small number of cases, and data on each case were collected and analysed. The whole experiment was controlled through a World Wide Web site. Results— A total of 56 case consultations on 34 different cases were exchanged. The average case document contained seven images, and contained 1.97 Mbytes of data. For cases in which data were recorded, average case preparation and remote consultation time was 55 minutes and 9.2 minutes, respectively. Transmission times averaged 3.9 minutes. In subjective impressions, reservations were expressed in several cases regarding the confidence that could be given to the diagnosis from the images presented. Conclusions —Remote consultation by telepathology via the Internet is now technically feasible and reasonably user friendly, but is only suitable as a method of disease diagnosis in some cases.